IMPLEMENTASI E – BUDGETING SEBAGAI UPAYA PENINGKATAN TRANPARANSI DAN AKUNTABILITAS PEMERINTAH DAERAH KOTA BINJAI - Anggi Pratama Nasution (Jurnal Akuntansi Bisnis dan Publik, 2019)
This research is intended to the Government at Binjai City of North Sumatra. Application of egovernance at regional work unit (SKPD) aims to strive the improvement of work performance based on several principles on good corporate governance (GCG) such as transparency and accountability on the government of Binjai City. Furthermore, this test is done by taking data to use questioners for all regional work (SKPD) in Binjai City. There are 52 people as budget user or authorthen the data is processed using some descriptive analysis methods. The result of research stated that even though the relation e budgeting is low with the accountability and transparency but the level of achievement of the use e-bugdeting has been reached well in attempting to increase the function of transparency and accountability so it is concluded that the role of system e-budgeting in increasing value of transparency and accountability on the government of Binjai City has been achieved.